DILEMA BUFFER STATE: ANALISIS KEBIJAKAN IMIGRASI MEKSIKO DI BAWAH TEKANAN DIPLOMASI KOERSIF AS THE BUFFER STATE DILEMMA: ANALYSIS OF MEXICAN IMMIGRATION POLICY UNDER PRESSURE FROM US COERCIVE DIPLOMACY - Zaskia Nasaru (Journal Of Social And Political Science, 2026)
This journal analyzes Mexico's role as a buffer state in managing migration flows from Central America to the United States from 2017 to 2025. Due to its strategic geographical location and high economic dependence on the US, Mexico has been subject to coercive diplomatic pressure in the form of tariff threats, the Remain in Mexico policy, the Zero Tolerance policy, military deployment, and mass deportations. Using a descriptive qualitative approach and a normative analysis of policy documents and official reports, the study concludes that this external pressure has prompted Mexico to implement stricter domestic policies, including the deployment of the National Guard, the construction of migrant detention centers, and limitations on access to asylum procedures. This creates a strategic dilemma for Mexico, pitting the need to maintain bilateral stability with the US against the need to uphold national sovereignty and commitments to human rights. At the local level, these policies have led to a humanitarian crisis in border regions, increased burdens on public services, and social and political tensions. The journal emphasizes the importance of reformulating Mexico's migration policies through institutional capacity building, developing the southern regions, and taking a multilateral approach that emphasizes shared responsibility and the fair protection of migrants.